Rusydi Zainal Abdi Batubara: Penggiat Pendidikan Agama Islam dari Mandailing Natal Tahun 1988-2020 - Yunita Yunita; Zul Asri (PAMA Aksara, 2021)
The purpose of this study is to reveal the life history of Rusydi Zainal Abdi Batubara as an activist for Islamic Religious Education from Mandailing Natal and to explain his career in establishing several Islamic boarding schools. This study uses historical research methods through four stages, namely, first heuristics is the stage of collecting data from oral and written sources, secondly source criticism is internal criticism and external criticism, third analysis and interpretation or interpretation of selected sources, and fourth, historiography is to describe the results of research in the form of scientific writing in accordance with the rules of historical research. The result of this research is that Rusydi Zainal Abdi Batubara is an Islamic religious education activist from Mandailing Natal, who started his career in Malaysia as a preacher and teacher, then in Mandailing Natal. In addition, he also founded the Issiyah Islamic boarding school in Malaysia in 1994, in 2002 founded the Nadwa Islamic Boarding School in Mandailing Natal, precisely in Air Apa Village, Sinunukan District, after that in 2017 founded the Daarul Abdil Mukhlisin Islamic Boarding School in Pulo Padang, Lingga Bayu District, Mandailing Natal district.